2015
DOI: 10.1152/jn.00097.2015
|View full text |Cite
|
Sign up to set email alerts
|

Discrete coding of stimulus value, reward expectation, and reward prediction error in the dorsal striatum

Abstract: To investigate how the striatum integrates sensory information with reward information for behavioral guidance, we recorded single-unit activity in the dorsal striatum of head-fixed rats participating in a probabilistic Pavlovian conditioning task with auditory conditioned stimuli (CSs) in which reward probability was fixed for each CS but parametrically varied across CSs. We found that the activity of many neurons was linearly correlated with the reward probability indicated by the CSs. The recorded neurons c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 48 publications
(55 reference statements)
1
23
0
Order By: Relevance
“…The activity in the reward period remained unaltered even in omission trials. Similar neuronal signals have been reported in the striatum in mammals (Tremblay et al, 1998; Kim et al, 2009; Oyama et al, 2015). Note, however, that in the study by Kim et al (2009), the researchers expected the neurons to code the action value rather than the state value.…”
Section: Discussionsupporting
confidence: 82%
“…The activity in the reward period remained unaltered even in omission trials. Similar neuronal signals have been reported in the striatum in mammals (Tremblay et al, 1998; Kim et al, 2009; Oyama et al, 2015). Note, however, that in the study by Kim et al (2009), the researchers expected the neurons to code the action value rather than the state value.…”
Section: Discussionsupporting
confidence: 82%
“…Whereas some previous work report activity in dorsal striatum to be unaffected by cue onset (Berke, ; Kimchi et al ., ; Root et al ., ), other work suggests cue‐triggered activity in NAc depends on the subsequent behaviour or outcome of the trial (Nicola et al ., ; Roitman & Loriaux, ). In addition, dorsal striatal and NAc neurons have been previously shown to modulate their activity according to the rat's actions in previous trials (Kim et al ., ; Oyama et al ., ). Consistent with this, here, we found that cue‐related excitatory activity was increased after previous errors (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that RPE signals can be found in multiple brain areas such as prefrontal cortex, the striatum, GPi, lateral habenula and RMTg (Asaad and Eskandar, 2011; Bromberg-Martin and Hikosaka, 2011; Hong and Hikosaka, 2008; Matsumoto and Hikosaka, 2007, 2008; Oyama et al, 2015). This is potentially because RPE signals are useful for a variety of behaviors outside of reinforcement learning (Den Ouden et al, 2012; Schultz and Dickinson, 2000).…”
Section: Discussionmentioning
confidence: 99%